An Exploration of the Skills and Knowledge of the Accounting Profession - Palacio-Fierro, Andrés (2023)
At present, the business sector has introduced significant changes in its structure that require qualified personnel in every area of knowledge. In this sense, professionals need to develop certain types of skills and knowledge that make them suitable candidates for their assigned roles. In this regard, the accounting profession within organizations has reached a significant level of importance, since it is responsible for the proper care and management of their finances. The aim of the present study is to analyze the perception that accountants show regarding the competencies and knowledge that a professional accountant needs. To achieve this goal, cross-sectional descriptive-explanatory research was applied with non-probabilistic and non-experimental sampling. The main results show that values are a highly relevant aspect for the development of the accounting profession, since it encompasses aspects related to work responsibility and ethics. In conclusion, an accountant must have a comprehensive training that allows them to respond to any assigned function and, above all, to efficiently respond to the different requirements demanded by their profession.